2019
DOI: 10.1186/s12931-019-1169-9
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the IPF-specific version of St. George’s Respiratory Questionnaire

Abstract: Background Patients with idiopathic pulmonary fibrosis (IPF) have impaired health-related quality of life (HRQL). To measure HRQL, an IPF-specific version of the St. George’s Respiratory Questionnaire (SGRQ-I) was developed, but not sufficiently validated. This study aimed to assess the validity (i.a. known-groups validity and concurrent validity) and test-retest reliability of SGRQ-I in IPF patients with different disease durations. Methods Patients with IPF were conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 31 publications
1
52
1
Order By: Relevance
“…As a result of measurement error on two measures, correlations between changes in scores are expected to be smaller. This may explain the generally weaker correlations in this longitudinal study compared to the cross-sectional studies on SGRQ-I and K-BILD [7][8][9][10]. DLCO showed the weakest associations to SGRQ-I and K-BILD in both analyses.…”
Section: Discussioncontrasting
confidence: 67%
See 3 more Smart Citations
“…As a result of measurement error on two measures, correlations between changes in scores are expected to be smaller. This may explain the generally weaker correlations in this longitudinal study compared to the cross-sectional studies on SGRQ-I and K-BILD [7][8][9][10]. DLCO showed the weakest associations to SGRQ-I and K-BILD in both analyses.…”
Section: Discussioncontrasting
confidence: 67%
“…Both methods indicated that SGRQ-I and K-BILD responded to changes in all HRQL and most physiological anchors; scores of the two instruments changed in concordance with changes in the anchors. The weaker correlations to physiological than to HRQL anchors were expected, as cross-sectional studies of K-BILD and SGRQ-I have shown similar results [7][8][9][10]. As a result of measurement error on two measures, correlations between changes in scores are expected to be smaller.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Cough-related QOL, assessed by cough questionnaires including not limited to cough visual analogue scale (VAS), [ 21 ] Leicester cough questionnaire (LCQ), [ 22 ] Cough Quality of Life Questionnaire (CQLQ), [ 4 ] St. Georges Respiratory Questionnaire (SGRQ). [ 23 ]…”
Section: Methodsmentioning
confidence: 99%